2005
DOI: 10.1524/ract.2005.93.9-10.605
|View full text |Cite
|
Sign up to set email alerts
|

Sorption of99MoO42-ions on commercial hydrotalcites

Abstract: 99m Tc generator / Hydrotalcite / Calcined hydrotalcite / Molybdenum Summary. 99 MoO 4 2− sorption behavior on 3 commercial hydrotalcites, produced by Sasol Chemie, was studied through batch experiments. Only one of them showed high sorption capacity. This product, the MG70 was identified by XRD diffraction analysis as hydrotalcite (Mg 6 Al 2 (OH) 16 CO 3 ·4H 2 O), while the other two, MG50 and MG30, were identified mainly as magnesium aluminum hydroxide hydrate, MgAl 2 (OH) 14 ·3H 2 O. Calcined MG70 (CMG70) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…A study has been made of the adsorption of americium onto a-alumina 220 and of [ 99 Mo]molybate anions onto hydrated aluminas. 221 Similarly it has been found that uranyl cations are adsorbed by hydroxyapatite, 222 that iodine, caesium and strontium radionudlides are adsorbed onto hydroxyphosphates 223 and that rare earth, neptunium and plutonium ions can be adsorped 224 onto calcite. Stronium-90 cations are adsorbed 225 onto the structurally similar magnesite and also onto kaolinite.…”
Section: Adsorptionmentioning
confidence: 97%
“…A study has been made of the adsorption of americium onto a-alumina 220 and of [ 99 Mo]molybate anions onto hydrated aluminas. 221 Similarly it has been found that uranyl cations are adsorbed by hydroxyapatite, 222 that iodine, caesium and strontium radionudlides are adsorbed onto hydroxyphosphates 223 and that rare earth, neptunium and plutonium ions can be adsorped 224 onto calcite. Stronium-90 cations are adsorbed 225 onto the structurally similar magnesite and also onto kaolinite.…”
Section: Adsorptionmentioning
confidence: 97%
“…A magnesium/aluminum LDH known as hydrotalcite [Mg 6 Al 2 (OH) 16 CO 3 • 4H 2 O] has been evaluated as a separations medium for 99m Tc for medical isotope applications (Serrano et al 2005, Dash et al 2013. As a 99m Tc generator, 99 MoO 4 2is loaded onto the hydrotalcite.…”
Section: Layered Double Hydroxidesmentioning
confidence: 99%
“…With the thermal neutron flux Φ > 5.1013 n ⋅ cm −2 ⋅ sec −1 available in the majority of the research reactors around the world, it is justified that the column packing material of ≥ 172 mg Mo/g should be developed for the effective use in the process of 99m Tc-generator production. Several sorbents, such as acidic/basic alumina, hydrous zirconium oxide, hydrous titanium oxide, manganese dioxide, silica gel, hydrotalcites, inorganic ion-exchange materials (zirconiumsalt form of zirconium-phosphate ion exchanger), hydroxyapatite, mixed oxide of tetravalent metals, and diatomaceous earth, have been developed/investigated over the years [20,[133][134][135][136][137][138][139][140][141]. These sorbents are only used for the production of fission- 99 Mo-based 99m Tc-generators but they are unsuitable for 99m Tc-generators loaded with 99 Mo of low specific activity due to their low Mo-adsorption capacity (<100 mg Mo/g).…”
Section: High Mo-loading Capacity Column-based 99m Tc Recovery and Rementioning
confidence: 99%